Analisis Kesalahan Siswa dalam Menyelesaikan Soal Matematika Pada Penggunaan Turunan Fungsi Berdasarkan Langkah-Langkah Polya di Sma YPPK Taruna Dharma Jayapura - Anastasia Nanci Sawitto; Yosefin Rianita Hadiyanti; Pitriana Tandililing (LPPM Press, 2014)
This study is a descriptive study using a qualitative approach. The purpose of this study isto describe the location of the fault response and the factors that cause the errors studentsas well as to find out a solution how to solve the error response of the student in solvingproblems based on the use of derivative function Polya steps consisting of four steps,namely problem solving (1) understanding the problem, (2) completion of the plan, (3)implementation of the settlement plan. The result shows that: the mistakes made by thestudents in understanding the problem that is not writing down what is known and what isbeing asked of the problem as well as one in writing what is being asked of the matter; themistakes made by students in the completion of the plan that did not make the settlementplan; error in executing the settlement plan that does not transcribe information on thenumber line, one in determining the derivative function, one in the wrong in the countingprocess and write the final answer of the question; and the mistakes made by students thatthe students do not check back answers that have been obtained.